Elevated pre-pregnancy testosterone is associated with gestational diabetes mellitus: an observational cohort study - Luo, Xufan; Li, Meng; Long, Yan; Ying, Chunmei; Yue, Chaoyan (Frontiers in Endocrinology, 2025)
ContextPre-pregnancy testosterone increase may be closely related to the occurrence of gestational diabetes mellitus (GDM).ObjectiveOur aim is to explain the relationship between pre-pregnancy testosterone levels and the risk of GDM and provide evidence for early clinical warning.MethodsWe conducted a retrospective cohort study on 4174 parturient. The exposure factor is pre-pregnancy testosterone, with the primary outcome was GDM (A1+A2) and the secondary outcome was GDM A2. We used trend testing, multivariate logistic regression models, smooth curve fitting, and age and BMI for subgroup analysis and interaction analysis to evaluate the relationship and odds ratio between different pre-pregnancy testosterone levels and GDM risk.ResultsElevated levels of pre-pregnancy testosterone are closely related to the onset of GDM Compared with the control group, women with testosterone levels between Q4 nmol/L had an OR value of 1.76 (95% Confidence Interval: 1.38,2.25) for GDM (A1+A2). The OR value for GDM A2 is 2.26 (95% CI: 1.27,4.00). In terms of sensitivity analysis, it was also observed that elevated pre-pregnancy testosterone increased the risk of GDM, especially in the age<35 and BMI<24 groups. Pre-pregnancy testosterone had a greater effect on GDM A2, with OR values of 1.42 (95%CI: 1.04,1.94) and 1.86 (95% CI: 1.30,2.66).ConclusionPre-pregnancy testosterone testing is associated with the risk of developing GDM, and women age<35 or BMI<24 need to pay more attention to pre-pregnancy testosterone. Pre-pregnancy testosterone can serve as a potential biomarker for risk stratification of GDM.